E-learning in medical education: Challenges and benefits in the perception of medical students during COVID-19 pandemic - Banur Raju Archana; Sampath Sangeetha (Journal of Clinical and Scientific Research, 2023)
Background: The Government of India declared nationwide lockdown due to the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) disease (COVID-19) pandemic. In order to continue regular classes, educational institutions tried various teaching, learning methods and started online classes. Methods: A descriptive, online questionnaire-based survey was conducted among undergraduate medical students studying at a medical college to evaluate the effectiveness, advantages and disadvantages of e-learning classes conducted for medical students during the COVID-19 pandemic. A questionnaire was prepared using Google Forms and students were asked to answer questions with the most appropriate response. Results: A total of 560 MBBS undergraduate students took part in the study. The survey was carried out after 6 months of online classes. The study result shows that e-learning is equally effective as regular face-to-face learning in increasing knowledge, social competences, understanding subject and meeting individual learning needs. However, e-learning is ineffective in increasing clinical skills and effective communication compared to regular face-to-face learning. Major advantage of e-learning is the ability to stay at home and lack of clinical skills is a major disadvantage. Conclusions: Implementation of distance e-learning in medical education is challenging, especially in developing countries like India. E-learning reported increasing knowledge, easy access, better environment. But lack of clinical skills, technical problems, mental health are major barriers to e-learning in medical education. Although e-learning is the best alternative in the present scenario, it cannot replace traditional teaching method. It can be used along with regular face-to-face learning to make teaching more effective.